2016
DOI: 10.1021/acsphotonics.6b00515
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Refraction and Nondiffractive Bessel-Beam Generation of Terahertz Waves through Transmission-Type Coding Metasurfaces

Abstract: Coding metasurfaces, composed of an array of coding particles with discrete phase responses, are encoded with predesigned coding sequences to manipulate wavefronts of electromagnetic (EM) waves and realize novel functionalities such as anomalous beam deflection, broadband diffusion, and polarization conversion. Such a new concept can be viewed as a bridge linking metamaterial and digital codes, yielding the investigation of metamaterials from a digital perspective and eventually the realization of real-time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
128
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(128 citation statements)
references
References 52 publications
0
128
0
Order By: Relevance
“…Few‐layer metasurfaces can not only realize the beam deflectors, but also realize the metalenses, vortex beam generators, Bessel‐beam generators, coding metasurfaces, phase holograms, virtual shaping, and some other phase manipulation devices. Metalenses can be designed by imposing a hyperboloidal transmission/reflection phase profile on the metasurfaces to convert incident planar wavefronts into spherical ones .…”
Section: Prominent Applications In Few‐layer Metasurfacesmentioning
confidence: 99%
“…Few‐layer metasurfaces can not only realize the beam deflectors, but also realize the metalenses, vortex beam generators, Bessel‐beam generators, coding metasurfaces, phase holograms, virtual shaping, and some other phase manipulation devices. Metalenses can be designed by imposing a hyperboloidal transmission/reflection phase profile on the metasurfaces to convert incident planar wavefronts into spherical ones .…”
Section: Prominent Applications In Few‐layer Metasurfacesmentioning
confidence: 99%
“…However, the high Ohmic loss of plasmonic metasurface results in a significantly suppressed efficiency. The newly developed dielectric and multilayered plasmonic metasurfaces can drastically improve the efficiency, but result in the complexity of design and fabrication, hindering their practical applications. To meet the requirements of future THz communications, exploring planar THz photonics with simple configuration, low loss, and low cost is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…However, an additional horn antenna was required to launch the reference wave for the phase compensation, which increases the overall complexity of the Bessel antenna. In recent years, some transmission‐type coding metasurfaces have been developed with predesigned coding sequences to manipulate the wavefront of electromagnetic waves . A latest study reported that a novel transmission‐type coding metasurface had the ability to bend the nondiffractive Bessel beam.…”
Section: Introductionmentioning
confidence: 99%
“…However, this coding metasurface had a complicated three‐layer structure. These state‐of‐the‐art Bessel deflection antennas were designed by using the scalar method, and the Bessel beam in different oblique directions was controlled by changing the frequency . However, for the fixed‐frequency and/or narrow‐band systems, these Bessel deflection antennas may not be good candidates.…”
Section: Introductionmentioning
confidence: 99%